2017
DOI: 10.1007/s11060-017-2453-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiation impairs normal developmental cortical thinning in medulloblastoma

Abstract: Medulloblastoma patients are treated with surgery, radiation and chemotherapy. Radiation dose to the temporal lobe may be associated with neurocognitive sequelae. Longitudinal changes of temporal lobe cortical thickness may result from neurodevelopmental processes such as synaptic pruning. This study applies longitudinal image analysis to compare developmental change in cortical thickness in medulloblastoma (MB) patients who were treated by combined modality therapy to that of cerebellar juvenile pilocytic ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In comparison to PiA, MB patients show decreased cerebral blood flow [18], more evident leukoencephalopathy [30], and less cortical thinning throughout development [41].…”
Section: Site-and Tumor-specific Neurocognitive Dysfunction and Imagi...mentioning
confidence: 92%
“…In comparison to PiA, MB patients show decreased cerebral blood flow [18], more evident leukoencephalopathy [30], and less cortical thinning throughout development [41].…”
Section: Site-and Tumor-specific Neurocognitive Dysfunction and Imagi...mentioning
confidence: 92%
“… 111 , 112 Cortical thinning may be dose dependent and different parts of the cortex may be more susceptible. 114 , 115 In addition, cerebral microbleeds was found to be more frequent in children treated with cranial radiotherapy and could be a contributing factor to worse neurocognitive function. 116 , 117 In the Rad-Art study, cerebral microbleeds was found to occur in almost half of children treated with cranial radiotherapy 5 years post treatment and was associated with worse executive function and performed worse in delayed recall, verbal learning, attention, and working memory.…”
Section: Toxicities Of Cns Directed Radiotherapy In the Pediatric Pop...mentioning
confidence: 99%